The Negative Ontology of Queer Inspiration: The Contribution of Georg Simmel - Sonzogni, Barbara; D’Ambrosio, Gabriella (Simmel Studies)

(untitled) (Edizioni ETS, 2025)
This paper develops a relational account of queer subjectivity by bringing the sociology of Georg Simmel into dialogue with contemporary queer theory. Rather than treating Simmel as a precursor, the article mobilizes his conceptual framework – particularly the notion of Wechselwirkung – as a resource for rethinking identity as a process emerging from dynamic social relations. The central argument is that Simmel’s formal sociology offers a relational ontology structurally compatible with queer critiques of identity as fixed and self-identical. Through an analysis of key sociological forms – such as fashion, the stranger, and money – the paper shows how subjectivity is constituted, stabilized, and destabilized within specific configurations of social interaction. These figures reveal identity as a process of repetition, liminal belonging, and abstraction, rather than as a stable ontological ground. By integrating Simmelian sociology with insights from queer theory, the article contributes to both fields. It expands the interpretative potential of Simmel’s work beyond its traditional reception, while providing queer theory with a sociologically grounded account of relational subjectivity. In doing so, it advances the idea of a negative ontology in which identity is understood as an open, processual, and continually negotiated form.